Electrolyte as a panacea to contemporary scientific world of super-capacitive energy: A condense report. (1st August 2022) - Dhanda, Monika; Arora, Rajat; Ahlawat, Simran; Nehra, S.P.; Lata, Suman
Abstract: The role of an electrolyte is quite indispensable towards the supercapacitors' performance including the essential parameters like power density, energy density, specific capacitance, cyclic stability, rate performance and can make a noticeable difference altogether. In this paper, an overview about the performance characteristics of various electrolytes towards energy storage is explored. Additionally, the classification of the several present-day electrolytes into different categories such as aqueous, organic, ionic liquid, solid and quasi-state electrolyte, hydrogel polymer electrolyte, organo-gel electrolyte, water in salt electrolyte and green electrolytes is rationally illustrated. The article encompasses the important parameters to be considered while selecting an electrolyte for supercapacitors such as thermal stability, electrochemical stability, energy and power densities, equivalent series resistance, capacitance, salt as well as solvent effect and many more. Even, it confers about redox mediators playing a key role in enhancing the electrochemical behavior of supercapacitors. We assure that the paper can lead about the key aspects for selection, proposed observance about good capacitance data and reaction mechanism occurring at electrified interface and with future aspects, it can invite a bulk readability. Highlights: Role and classification of electrolytes towards super-capacitive energy explored. Article emphasizes about key features of diverse electrolytes for energy storage. It focuses on correlation among different energy parameters with the electrolyte. It also describes the role of redox mediators in enhancing the energy performance. It underpins the selection criteria for better capacitance of various electrolytes.